Sexuality Education: Counselors from the Perspective of a Biographical Professional Model - Manuel Arturo Fallas-Vargas; Cindy Vanessa Artavia-Aguilar; Alejandra Gamboa-Jiménez (Universidad Nacional, Costa Rica, 2012)
This paper discusses how important it is for the contemporary society to enhance knowledge about sexuality for the purpose of an effective sexuality experience within a framework of respect to the sexual biography of individuals, based on the relational ethics. For this, we believe in a comprehensive, democratic, tolerant, open sexuality education within the educational processes, throughout all the human development stages. Counseling is one of the professional sectors called to work on this kind of education. Counselors are required to identify the approaches and models they were educated with, which have marked their activity in this field. In this way, they will be able to evaluate, strengthen and learn new skills in the personal, attitudinal, and conceptual areas; they will also have a better perspective on the diversity of those requiring his/her professional services; and, in the procedural field, they will be able to put into practice the counseling intervention strategies and techniques in sexuality that will impact their professional activity.